Tunable physics through coordination chemistry: formation on oxide surface of Ti and Al chelates with 3-hydroxyflavone capable of electron injection and light emission. Issue 48 (24th November 2022) - Solomon, Getachew; Landström, Anton; Rotta Loria, Silvia; Bolli, Eleonora; Mezzetti, Alberto; Facibeni, Anna; Cattarin, Sandro; Mezzi, Alessio; Protti, Stefano; Kaciulis, Saulius; Zavelani-Rossi, Margherita; Concina, Isabella
Abstract : The optoelectronic features of 3-hydroxyflavone (3HF) self-assembled on the surface of an n-type semiconducting metal oxide (TiO2 ) and an insulator (Al2 O3 ) are herein investigated. Abstract : The optoelectronic features of 3-hydroxyflavone (3HF) self-assembled on the surface of an n-type semiconducting metal oxide (TiO2 ) and an insulator (Al2 O3 ) are herein investigated. 3HF molecules use the coordinatively unsaturated metal ions present on the oxide surface to form metal complexes, which exhibit different behaviors upon light irradiation, depending on the nature of the metal ion. Specifically, we show that the photoluminescence of the surface species can be modulated according to the chemical properties of the complex ( i.e. the binding metal ion), resulting in solid-state emitters in a high quantum yield (about 15%). Furthermore, photoinduced charge injection can be promoted or inhibited, providing a multifunctional hybrid system.